Understanding How Fuel Treatments Interact With Climate and Biophysical Setting to Affect Fire, Water, and Forest Health: A Process-Based Modeling Approach - Burke, William D.; Tague, Christina; Kennedy, Maureen C.; Moritz, Max A. (Frontiers in Forests and Global Change, 2021)
Fuel treatments are a key forest management practice used to reduce fire severity, increase water yield, and mitigate drought vulnerability. Climate change exacerbates the need for fuel treatments, with larger and more frequent wildfires, increasing water demand, and more severe drought. The effects of fuel treatments though can be inconsistent and uncertain and can be altered by a variety of factors including the type of treatment, the biophysical features of the landscape, and climate. Variation in fuel treatment effects can occur even within forest stands and small watershed management units. Quantifying the likely magnitude of variation in treatment effects and identifying the dominant controls on those effects is needed to support fuel treatment planning directed at achieving specific fire, water, and forest health goals. This research aims to quantify and better understand how local differences in treatment, landscape features, and climate alter those fuel treatment effects. We address these questions using modeling methods, specifically the Regional Hydro-Ecological Simulation System (RHESSys). We ran 13500 scenarios covering a broad range of fuel treatment, biophysical, and climate conditions, for the Southern Sierra Nevada of California. We find nontrivial variation in fuel treatment effects across fuel treatment type, biophysical, and climate parameters on stand carbon, net primary productivity, evapotranspiration, and fire-related canopy structure variables. Estimates range substantially, from increases (1% – 48%) to decreases (-13% – 175%) compared to untreated scenarios. The relative importance of parameters varies by response variable, however, fuel treatment method & intensity, plant accessible water storage capacity, and vegetation type all consistently demonstrate a large influence across all response variables. These parameters interact to produce non-linear effects. Results show that projections of fuel treatment effects based on singular mean parameter values (such as mean plant available water capacity), provide a limited picture of potential responses. Our findings emphasize the need for a more complete perspective when assessing expected fuel treatment outcomes, both their effects, and the interacting biophysical and climatic parameters that alter those effects. This research also serves as a demonstration of methodology to assess the likely variation in potential effects of fuel treatments for a given planning unit.